Animal abuse, vicarious violence and gender violence: The integration of animal resources in the integral intervention in gender violence in the intimate partner or ex-partner environment - F. Sánchez, Soraya; Mateos Casado, Cristina; Tajahuerce Ángel, Isabel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This investigation presents animal abuse as a manifestation of vicarious violence in the field of gender violence. It is contextualized within the framework of the theoretical current of Ecofeminism and the contributions of the main works published in Spain about the relation between animal abuse and gender violence. Three the pioneer Spanish intervention resources that work on maintaining the animal-human link in the protection and recovery of women victims-survivors of gender violence in the field of the couple or former partner are presented and analyzed in this paper.